Lesions of the Suprachiasmatic Nucleus Eliminate the Daily Rhythm of Hypocretin-1 Release - Zhang, Shengwen; Zeitzer, Jamie M.; Yoshida, Yasushi; Wisor, Jonathan P.; Nishino, Seiji; Edgar, Dale M.; Mignot, Emmanuel (Sleep (New York, N.Y.), 2004)
Hypocretins (orexins) are involved in the sleep disorder narcolepsy. While hypocretin-1 has a daily oscillation, little is known regarding the relative contribution of circadian and homeostatic components on hypocretin release. The effect of lesions of the suprachiasmatic nucleus (SCN) on hypocretin-1 in the cerebrospinal fluid (CSF) was examined. SCN-ablated (SCNx) and sham-operated control rats were implanted with activity-temperature transmitters. Animals were housed individually under 1 of 3 lighting conditions: 12-hour:12-hour light:dark cycle (LD), constant light (LL), and constant darkness (DD). Lesions were verified histologically and shown not to affect hypocretin-containing cells. Hypocretin-1 concentrations in the CSF were determined every 4 hours using radioimmunoassays. Control animals displayed robust circadian (LL, DD) and diurnal (LD) fluctuations in CSF hypocretin-1, locomotor activity, and temperature. Peak CSF hypocretin-1 was at the end of the active period. Activity, temperature, and CSF hypocretin-1 were arrhythmic in SCNx animals in LL and DD. In LD, a weak but significant fluctuation in activity and temperature but not CSF hypocretin-1 was observed in SCNx animals. We also explored correlations between CSF hypocretin-1, CSF corticosterone, and locomotor activity occurring prior to CSF sampling in arrhythmic SCNx rats under constant conditions. Significant correlations between hypocretin-1 and activity were observed both across and within animals, suggesting that interindividual and time-of-the-day differences in activity have significant effects on hypocretin release in arrhythmic animals. No correlation was found between CSF hypocretin-1 and corticosterone. Hypocretin-1 release is under SCN control. Locomotor activity influences the activity of the hypocretin neurons.